2016
DOI: 10.1080/13554794.2016.1216571
|View full text |Cite
|
Sign up to set email alerts
|

The suppression effect in visuospatial and verbal working memory span tasks in patients with Alzheimer’s disease: a 2-year follow-up study

Abstract: This study adapted a new task to assess visuospatial and verbal working memory impairments in patients with Alzheimer Disease (AD), including an executive strategy of information suppression. The aim was to examine the visuospatial and verbal difficulties, and additionally to explore the average sex differences, during a 2-year follow-up study. The results indicated that patients with AD showed a significantly lower performance, compared with healthy elderly controls, especially with the suppression of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
4
5
1
Order By: Relevance
“…The results of the present research corroborate those previously found by other authors [10, 14]; yet, this study has expanded the visuospatial tasks in the MCI group and has added the differences between sexes that were obtained.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the present research corroborate those previously found by other authors [10, 14]; yet, this study has expanded the visuospatial tasks in the MCI group and has added the differences between sexes that were obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the differences between the sexes in the healthy elderly group, both in the present study and in the study by Elosúa et al [14], a lower average performance was obtained in the group of women than in the group of men, although in neither study were these differences significant. These results point in the same direction as other previous studies [12, 23, 24, 25].…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations